Innovative Cultural Tourism in European Peripheries - Borowiecki, Karol Jan; Fresa, Antonella; Martín Civantos, José María (Routledge Research in the Creative and Cultural Industries, 2025)
Cultural tourism can play an important role in social and territorial cohesion. Focusing on European peripheral regions, this book illuminates the importance of local communities in heritage management for sustainable development. This book provides insights into the use of innovative business models and tools, such as ecosystem services contracts and digital narrative platforms, to enhance the sustainability and economic development of peripheral and marginal destinations. Additionally, this book addresses the value of data collection and analysis in cultural tourism and provides insights into participatory models and approaches that contribute to sustainable tourism development. With contributions from a pan‑European range of expert scholars and practitioners, this book serves as an essential resource for researchers, professionals, and anyone with an interest in tourism, and the cultural and creative industries. The Open Access version of thi book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial- No Derivatives (CC-BY-NC-ND) 4.0 license.